Kajian Kelangkaan Minyak Goreng Akibat Penimbunan Terjadinya Penimbunan Berdasarkan Undang-Undang Nomor 8 Tahun 1999 Tentang Perlindungan Konsumen - Muhammad Falih Abdi Nugroho; Jean N Sally (LPPM Universitas Ekasakti Padang, 2023)
One of the problems that often occurs in Indonesia is the problem of food shortages, one of which is cooking oil. This has a negative impact on the Indonesian people because their basic needs are decreasing. This is caused by many business actors hoarding cooking oil and reselling it at high prices to make a profit. Hoarding is defined as buying something and saving it so that the item decreases in society so that the price will increase and people will have difficulty meeting their basic needs. This kind of hoarding is prohibited because it is a crime and evidence of moral badness and makes it difficult for people to fulfill their daily needs. Humans in this case are focused on the continuity of consumer life in fulfilling their basic life needs. The researcher applies a normative juridical legal research approach, namely an approach that uses the legal positivist concept, which views law as identical to written norms created and promulgated by authorized institutions or officials. This legal concept is a normative system that is independent, closed, and apart from real social life.